Surgical treatment of intravenous leiomyomatosis involving the right heart: a case series. Issue 7 (July 2019) - Luo, Guangze; Pan, Hongrui; Bi, Jiaxue; Luo, Yudong; Zhu, Jiechang; Feng, Zhou; Fan, Hailun; Zhang, Yiwei; Dai, Xiangchen
Objective: This study was performed to investigate the surgical treatment of intravenous leiomyomatosis involving the right heart. Methods: The clinical data of five patients with intracardiac leiomyomatosis treated from April 2002 to October 2017 at a single center were retrospectively analyzed. Results: All five patients underwent successful intravenous and right atrial tumor removal via abdominal and inferior vena cava incisions. In three patients, these incisions were combined with thoracotomy and a right atrial incision, and in two patients, they were combined with uterine and bilateral fallopian tube and ovarian resection. One patient with advanced disease underwent a one-stage procedure and died thereafter. Of the remaining four patients who underwent follow-up for 1.5 to 12.0 years, one developed recurrence at 1 year postoperatively. The recurrent tumor, which was pathologically confirmed to be an intravenous leiomyoma, was removed via inferior vena cava and internal iliac vein incisions without subsequent recurrence. Conclusions: The main treatment goal for inferior vena cava leiomyomas involving the right heart is to first address the severe obstruction of cardiac blood flow and then pursue second-stage surgery. Concurrent thoracotomy appears unnecessary because moderately sized right heart tumors can be gently removed via the inferior vena cava.